An economic theory-based explanatory model of agricultural land-use patterns: The Netherlands as a case study. (October 2015) - Diogo, V.; Koomen, E.; Kuhlman, T.
Abstract: An economic theory-based land-use modelling framework is presented aiming to explain the causal link between economic decisions and resulting spatial patterns of agricultural land use. The framework assumes that farmers pursue utility maximisation in agricultural production systems, while considering alternative production options and making land-use decisions. Local utility is assumed to depend on a complex combination of different types of factors that together set the opportunities and constraints for different production options. The framework's ability to reproduce the current patterns is demonstrated for a case study in the Netherlands. The framework was implemented in a land-use modelling simulation tool rooted in economic theory, that was first specified according to the current trends in the driving forces assumed to steer land-use change. Alternative model specifications accounting for different sets of cash flows were implemented in order to explore the importance of uncertainties on model conceptualisation and structure. The allocation of agricultural land use was then simulated according to these specifications and the results were validated by comparing the simulated land-use patterns with observed ones. When cash flows accounting for path-dependency and land-use inertia were considered, the framework performed well in reproducing current patterns in the Netherlands, with a degree of correspondence of 82.2% in the pixel-by-pixel validation, up to 87.4% in the multiple resolution validation. Production costs and gross revenues seem to only partly explain the observed patterns, as shown by the lower degrees of correspondence (57.5% up to 65.0%) for the model specification solely accounting for these cash flows. In our case study, transportation costs did not seem to play a significant role in the allocation of agricultural land use, although that might be attributed to the relatively small size of the study area and the existence of a high-quality transport network. The model did not perform equally well for different production systems: land-uses specified at the crop level appeared to be particularly well allocated; those defined at the aggregated production system level performed poorer. The ability to link economic decision-making processes with the resulting agricultural land-use patterns, while incorporating complex interactions with different type of factors, implies that a coherent modelling approach for the simulation of future patterns of agriculture land use was established. This approach can be used to help policy-makers explore possible future socio-economic and environmental impacts resulting e.g. from climate change and/or policy reform, allowing them to devise strategies to cope with future challenges in agricultural systems. Highlights: Land-use model explaining the causal link between economic decisions and patterns Local utility maximisation in agricultural production systems is assumed. A combination of factors sets the opportunities and constraints for production options. A model was calibrated according to current trends and validated. A model performs well when accounting for path-dependency and inertia of land use.